Nanoparticles in gynecologic cancers: a bibliometric and visualization analysis - Zhou, Yunzhe; Chen, Lizhang; Wang, Tingting (Frontiers in Oncology, 2025)
BackgroundGynecological cancers are characterized by uncontrolled cell proliferation within the female reproductive organs. These cancers pose a significant threat to women’s health, impacting life expectancy, quality of life, and fertility. Nanoparticles, with their small size, large surface area, and high permeability, have become a key focus in targeted cancer therapy. The aim of this study is to review recent advancements in nanoparticles applied to gynecologic cancers, providing valuable insights for future research.MethodsWe retrieved all literature on nanoparticles in gynecologic cancers from the Web of Science Core Collection (WOSCC) database between January 1, 2004, and June 4, 2024. Data analysis and visualization were conducted using R software (version 4.4.0), VOSviewer (version 1.6.19.0), and CiteSpace (version 6.1).ResultsA total of 2,843 publications from January 1, 2004, to June 4, 2024 were searched. Over the past 20 years, there has been a significant increase in publications. The leading countries and institutions in terms of productivity are China and the Chinese Academy of Sciences. The most prolific author and the most co-cited author are Sood, A K and Siegel, Rl. The top journals are the International Journal of Nanomedicine (n=97), followed by ACS Applied Materials & Interfaces (n=72) and Journal of Materials Chemistry B (n=53). Keyword analysis shows current research focuses on two main areas: the application of nanoparticles for drug delivery and their broader applications in gynecologic cancers. Future research will likely focus on “silver nanoparticles,” “gold nanoparticles,” and “green synthesis.”ConclusionsOver the past two decades, nanoparticles have rapidly advanced in the field of gynecologic cancers. Research has primarily focused on the applications of nanoparticles in drug delivery and applications. Future trends point toward optimizing synthesis techniques and advancing preclinical studies to clinical applications, particularly for silver and gold nanoparticles. These findings provide valuable scientific insights for researchers.